Streptococcus bovis Meningitis and Hemorrhoids - Hewitt Smith, Adam; Sra, Harminder K.; Bawa, Sandeep; Stevens, Richard (Journal of clinical microbiology, 2010)
A previously fit 61-year-old woman presented to the hospital Accident and Emergency Department with a 2-day history of headache and malaise. Her headache had become rapidly more intense in the hours preceding admission, waking her from sleep, and was associated with severe neck stiffness, nausea, and vomiting. On examination, she was febrile (38.9°C), tachycardic (heart rate of 110 beats per min), was clinically mildly dehydrated, and drowsy, but orientated, and had marked meningism. There was no rash. There was no focal neurological abnormality, and fundoscopy was normal. Peripheral blood samples, including cultures, were taken, and treatment with intravenous (i.v.) ceftriaxone, acyclovir, and fluids was started. Urgent brain computed tomography (CT) scanning was normal. A fall in the patient’s blood pressure to 90/55 mm Hg prompted her transfer to the hospital’s High Dependency Unit, where a lumbar puncture was performed.
Keywords: Streptococcus bovis Meningitis; Hemorrhoids